Fatigue crack propagation behavior of IN718 superalloy aged with temperature/stress coupled field. (December 2021) - Deng, Hanzhong; Wang, Lei; Liu, Yang; Song, Xiu; Meng, Fanqiang; Yu, Teng
Highlights: The fatigue crack propagation resistance of IN718 alloy aged with stress was reduced. The accelerated coarse γ″ phase greatly increased the dislocation slip irreversibility. The smooth fracture surface of IN718 alloy was mainly caused by the coarse γ″ phase. Abstract: Fatigue crack propagation behavior of IN718 superalloy aged with or without stress was investigated. The alloy aged with stress exhibited a higher fatigue crack growth rate and a lower fatigue threshold compared to that without stress. Both the restricted dislocation planar slip and the decreased difference in orientation of the activated slip system between adjacent grains were promoted by coarse γ″ phases, which increased the local plastic deformation and reduced the crack deflection. The accelerated coarse γ″ phase caused by applied stress was the key factor for the degradation of fatigue crack propagation resistance of the alloy aged with stress.